2022
DOI: 10.1016/j.jad.2022.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-related impulsivity predicts increased anxiety and depression during the COVID-19 pandemic

Abstract: Introduction Emotion-related impulsivity, defined by poor constraint in the face of emotion, is related to internalizing symptoms, cross-sectionally and longitudinally. Internalizing symptoms, though, are profoundly tied to stress reactivity, and little is known about how emotion-related impulsivity relates to stress reactivity. Method Taking advantage of a sample that had completed measures of depression, anxiety, suicidal ideation, and two forms of emotion-related imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
2
18
1
Order By: Relevance
“…Notably, some studies have demonstrated the contribution of impulsivity to internalizing psychopathology [e.g., depression and anxiety; ( 28 , 29 )]. That impulsivity predicts anxiety severity has been found in both children ( 29 ) and adults ( 24 ) who are with internalizing or externalizing symptoms. Specifically, impulsivity would engage individuals in a highly emotional state in a stressful setting, causing anxiety symptoms ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, some studies have demonstrated the contribution of impulsivity to internalizing psychopathology [e.g., depression and anxiety; ( 28 , 29 )]. That impulsivity predicts anxiety severity has been found in both children ( 29 ) and adults ( 24 ) who are with internalizing or externalizing symptoms. Specifically, impulsivity would engage individuals in a highly emotional state in a stressful setting, causing anxiety symptoms ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…As proposed by some authors, interventions oriented to enhance mindfulness traits could be employed to prevent the negative consequences of impulsiveness on internalizing symptoms such as anxiety [ 48 ]. However, to our knowledge, little is known about the possible effects of mindfulness buffering the negative effects of impulsiveness on anxiety in female athletes.…”
Section: Discussionmentioning
confidence: 99%
“…This fact is especially important in athletes, in which emotion-related impulsiveness, such as negative urgency, could be especially important. In this regard, it has been recently found that impulsiveness in highly stressful situations could lead to anxiety reactions more easily [ 48 ]. Hence, individuals with higher levels of emotion-related impulsivity could be at high risk of developing higher levels of internalizing symptoms such as anxiety, due to their proneness to worry in ambiguous situations.…”
Section: Introductionmentioning
confidence: 99%
“…Third, in contrast to the first experiment, the second experiment was conducted during the COVID-19 pandemic (Exp1: March 25, 2019-May 20, 2019; Exp2: January 13, 2021-July 19, 2021), and individuals in general are expected to be in negative mental states (e.g., high stress, depression, and anxiety) (Brooks et al, 2020; Pfefferbaum & North, 2020). Given the close relationship between the on-going pandemic and health risk behaviors (Clay & Parker, 2020; Johnson et al, 2022; Park, Lee, Sul, & Chung, 2021), we cannot overlook a possibility that the null effect of intervention training at the second experiment is associated with the environmental change and accompanied changes of mental states.…”
Section: Discussionmentioning
confidence: 99%